TWEAK protects cardiomyocyte against apoptosis in a PI3K/AKT pathway dependent manner - Yang, Bin (Am J Transl Res, 2016)
Myocyte apoptosis is a key determinant of cardiac recovery and prognosis of patients with acute myocardial infarction (AMI). Tumor necrosis factor (TNF)-like weak inducer of apoptosis (TWEAK), a member of TNF superfamily, is a pro-inflammatory and pro-angiogenic cytokine implicated in physiological tissue regeneration and wound repair and is closely related to cardiac remodeling, dysfunction and fibrosis. However, the role of TWEAK and its receptor Fn14 in the cardiomyocyte apoptosis is still poorly understood. The present study aimed to investigate whether the TWEAK enhanced the cardiomyocyte apoptosis in AMI. The apoptosis of the cardiomyocyte cell line H9C2 was induced by hypoxia/reoxygenation. The apoptosis of H9C2 cells was evaluated by flow cytometry and caspase-3 activity assay under treatment with TWEAK at different concentrations. The phosphorylated signaling molecules and the expression involved in the surprising protection of TWEAK against the apoptosis with a dose-dependent manner (≥50 ng/ml). Furthermore, a rat myocardial ischemia and reperfusion (I/R) model was established by TWEAK preconditioning through injecting the TWEAK into the scar and border after ischemia immediately induced by ligating the left anterior descending coronary artery for 50 min and followed by different reperfusion times. The heart function was significantly improved in TWEAK preconditioning rats compared with controls as well as the infarct size was significantly reduced 21 days after reperfusion. Meanwhile, TWEAK protected the cardiac apoptosis by activation of cardioprotective signaling PI3K/AKT during I/R. Our findings suggest that TWEAK may represent a cardioprotective factor that inhibits the myocyte death of myocardial IRI.